A Phytoplasma- Associated Disease causing Degeneration of Toona ciliata- An Important Agroforestry Tree in India - Thakur, P.D.; Handa, Anil; Sharma, Usha; Jarial, Kumud; Bhaik, Ashutosh (Indian Journal of Agroforestry, 2020)
Toona ciliata (syn. Cedrela toona Roxb.) is one of the most important agroforestry tree of India, widely distributed in the sub-Himalayan track and valleys of outer region. Trees of this species are severely affected by witches' broom disease exhibiting symptoms of stunted growth, excessive bud sprouting, reduced leaf size and inhibition of flowering on diseased twigs. Plants of all age groups are found to be affected by the disease with an incidence as high as 100% in most of the areas of Himachal Pradesh. There is a great loss in young plants which is causing degeneration in the growth of this species. Phytoplasma etiology of this disease has been strongly suggested by conducting OAPI (4, 6- diamidino-2-phenyl indole HCl) tests and PCR assays. Fluorescence of phytoplasma-like particles was observed in phloem sections of diseased tissues but not in sections of healthy plants. Amplification using total nucleic acid extracted from the samples of diseased plants is a template resulted in an expected PCR product of 1.2 kb in size by using two phytoplasma specific universal primer pairs P11 P7 and R16F2n/R16R2 in nested PCR.